Reduction of harmonics emission of a WECS in the electrical grid using multilevel inverters - Maha Annoukoubi; Ahmed Essadki; Hammadi Laghridat; Tammou Nasser (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Wind energy conversion system (WECS) is composed of many non-linear power electronic sub systems, which contribute significantly in harmonic emissions that is a threat for the quality of electrical power. Hence, for a better integration of WECS in the electrical grid and in order to satisfy IEEE 519 standards, WECS must inject a quality power with a rate of total harmonics distortion (THD) that is less than 5%. Multilevel Inverters are an emerging solution for having a perfect sinusoidal output voltage with minimum harmonic content and lower switching losses than the two-level inverter so that only a smaller filter size is required. Thus, in this paper we are presenting a significantly improved results of the reduction of the grid injected current THD using three types of inverters (two-levels, three-levels NPC, and five-levels H-bridge cascade) for a WECS and comparing the THD performances of using each of the studied inverter. All results of THD are verified by a Fast Fourier transform simulation using MATLAB/Simulink.